Coquina and related hypersaline facies evolution in Shark Bay: morphology, chronology, processes and relationships - Correia Baptista da Silva, Rodrigo (Curtin University, 2014)
A Holocene coquina beach ridge system borders the hypersaline Hamelin Pool and L’Haridon Bight basins in Shark Bay. In Hamelin Pool, eastern and western shores have different degrees of vulnerability to the typically northwest approaching storms. Aerial imagery, GPR profiles, radiocarbon chronology and sedimentological data were used to delineate a depositional and evolutionary model for bioclastic beach-ridge deposits in Hamelin Pool eastern and western shores by assessing their internal and external architecture, facies and radiocarbon ages.